Tinjauan Teologis terhadap Peran Ganda Pengusaha-Pendeta : Antara Panggilan Ilahi dan Kepentingan Duniawi (Jurnal Pendidikan Agama dan Teologi, 2025)
The phenomenon of charismatic pastors who simultaneously serve as merchants represents an increasingly common reality in contemporary Christian ministry, especially within urban contexts where economic and spiritual dynamics are closely intertwined. This dual role reflects both opportunities and challenges for the church, raising important theological, ethical, and practical debates concerning the integrity of pastoral calling in the midst of worldly interests, material pursuits, and potential temptations. On the one hand, the bivocational model may provide pastors with financial independence, reducing the burden on congregations and offering broader opportunities for engagement with society. On the other hand, it also carries the risk of blurring the boundaries between ministry and commerce, thereby creating possible conflicts of interest, diminishing spiritual authority, and weakening the congregation’s trust in pastoral leadership. This study aims to analyze the dual role of pastor-merchant in the light of New Testament theology by identifying potential tensions, examining the relevance of pastoral ethics in guiding decision-making, and evaluating the impact of this dual vocation on the life and witness of the church. Methodologically, this research employs a qualitative literature study, reviewing biblical, theological, and pastoral ethics sources to formulate a comprehensive understanding. The findings suggest that pastoral ethics serve as a vital compass for pastor-merchants, ensuring that ministry remains pure, Christ-centered, and untainted by financial motives. The Apostle Paul provides a theological and practical model for bivocational ministry, demonstrating how secular work and spiritual service can coexist without compromising the divine calling. Furthermore, a healthy, transparent, and accountable leadership framework is essential for sustaining integrity and strengthening congregational trust. Ultimately, this study emphasizes that the identity of the church as “a chosen people, a royal priesthood” (1 Pet. 2:9) must remain the guiding principle, ensuring that the integration of pastoral vocation and marketplace involvement contributes positively to the church’s witness and relevance in modern society.